Hospital as a smoke-free workplace - Štěpánková, Lenka; Kostelecká, Lenka; Stejskalová, Veronika; Kalvachová, Milena; Králíková, Eva (Central European journal of public health, 2020)
OBJECTIVES: The primary aim of a hospital is to promote/improve and restore health, thus smoking, whether in its passive or active form, should be banned in all hospital premises for the benefit of employees and patients alike. The Global Network for Tobacco Free Healthcare Services (GNTH) is an international non-profit association formed in 1999. The GNTH's mission is to implement tobacco-free policies to create a healthy workplace and patients' environment; help physicians, nurses, and other healthcare workers to stop smoking; and educate all caregivers about tobacco dependence treatment and support them in providing smoking cessation interventions. METHODS: Implementation standards and a system of their self-audit for all participating hospitals were developed by the GNTH. We describe both the international and Czech networks, recommended methods for programme implementation and results of self-audit questionnaires completed by Czech participating hospitals. RESULTS: Worldwide, there are 19 national networks with 1,672 members including 56 gold forum members. To date, the largest network has been formed in France (670 members), followed by Spain (580) and Taiwan (209). After the first Czech institution (Prague-based General University Hospital) joined GNTH in 2010, the Czech Republic established its national network in 2017 currently comprising 10 members, of this number 1 gold, 3 silver and 6 bronze national certification level members. The main barriers to better outcomes in the Czech Republic include smoking on outdoor hospital grounds, lack of pharmacotherapy reimbursement and time, and inadequate staff education in the field of tobacco dependence treatment. CONCLUSIONS: The Global Network's mission is to advocate, recruit and enable healthcare services and professionals to implement and sustain effective tobacco management and cessation policies in accordance with the WHO Framework Convention on Tobacco Control (FCTC). A systematic approach supports the quality of care and treatment outcomes for patients as well as healthy workplace conditions for the staff.
Keywords: Smoking Cessation; Smoking Prevention; nekuřácká politika; hospital; tobacco-free health care; Humans; education; Hospitals; Smoke-Free Policy; odvykání kouření; prevence kouření; Workplace; pracoviště; health promotion; lidé; tobacco control; nemocnice